Repurposing Saquinavir for Host-Directed Therapy to Control Mycobacterium Tuberculosis Infection - Pires, David; Valente, Sofia; Calado, Marta; Mandal, Manoj; Azevedo-Pereira, José Miguel; Anes, Elsa (Frontiers in Immunology, 2021)
Despite the available antibiotics, tuberculosis (TB) has made its return since the 90's of the last century as a global threat mostly due to co-infection with HIV, to the emergence of drug resistant strains and the lack of an effective vaccine. Host-directed strategies could be exploited to improve treatment efficacy, contain drug-resistant strains, improve immune responses and reduce disease severity. Macrophages in the lungs are often found infected with Mycobacterium tuberculosis (Mtb) and/or with HIV. The long-term survival of lung macrophages infected with Mtb or with HIV, together with their ability to produce viral particles, especially during TB, makes these niches major contributors to the pathogenicity of the infection. Among the available drugs to control HIV infection, protease inhibitors (PIs), acting at post-integrational stages of virus replication cycle, are the only drugs able to interfere with virus production and release from macrophages during chronic infection. For Mtb we recently found that the pathogen induces a general down-regulation of lysosomal proteases, helping bacteria to establish an intracellular niche in macrophages. Here we found that the PI saquinavir, contrary to ritonavir, is able to induce an increase of endolysosomal proteases activity especially of cathepsin S in Mtb infected macrophages and during co-infection with HIV. Our results indicate that saquinavir treatment of infected macrophages led not only to a significant intracellular killing of Mtb but also: (i) to an improved expression of the HLA class II antigen presentation machinery at the cell surface; (ii) to increased T-lymphocyte priming and proliferation; and (iii) to the control of the inflammatory status. All together the results indicate saquinavir as a potential host directed therapy for tuberculosis.